Evolution of Termite Symbiosis Informed by Transcriptome-Based Phylogenies - Bucek, Ales; Šobotník, Jan; He, Shulin; Shi, Mang; McMahon, Dino P; Holmes, Edward C; Roisin, Yves; Lo, Nathan; Bourguignon, Thomas (Current biology, 2019)
Termitidae comprises ∼80% of all termite species [1] that play dominant decomposer roles in tropical ecosystems [2, 3]. Two major events during termite evolution were the loss of cellulolytic gut protozoans in the ancestor of Termitidae and the subsequent gain in the termitid subfamily Macrotermitinae of fungal symbionts cultivated externally in "combs" constructed within the nest [4, 5]. How these symbiotic transitions occurred remains unresolved. Phylogenetic analyses of mitochondrial data previously suggested that Macrotermitinae is the earliest branching termitid lineage, followed soon after by Sphaerotermitinae [6], which cultivates bacterial symbionts on combs inside its nests [7]. This has led to the hypothesis that comb building was an important evolutionary step in the loss of gut protozoa in ancestral termitids [8]. We sequenced genomes and transcriptomes of 55 termite species and reconstructed phylogenetic trees from up to 4,065 orthologous genes of 68 species. We found strong support for a novel sister-group relationship between the bacterial comb-building Sphaerotermitinae and fungus comb-building Macrotermitinae. This key finding indicates that comb building is a derived trait within Termitidae and that the creation of a comb-like "external rumen" involving bacteria or fungi may not have driven the loss of protozoa from ancestral termitids, as previously hypothesized. Instead, associations with gut prokaryotic symbionts, combined with dietary shifts from wood to other plant-based substrates, may have played a more important role in this symbiotic transition. Our phylogenetic tree provides a platform for future studies of comparative termite evolution and the evolution of symbiosis in this taxon.Termitidae comprises ∼80% of all termite species [1] that play dominant decomposer roles in tropical ecosystems [2, 3]. Two major events during termite evolution were the loss of cellulolytic gut protozoans in the ancestor of Termitidae and the subsequent gain in the termitid subfamily Macrotermitinae of fungal symbionts cultivated externally in "combs" constructed within the nest [4, 5]. How these symbiotic transitions occurred remains unresolved. Phylogenetic analyses of mitochondrial data previously suggested that Macrotermitinae is the earliest branching termitid lineage, followed soon after by Sphaerotermitinae [6], which cultivates bacterial symbionts on combs inside its nests [7]. This has led to the hypothesis that comb building was an important evolutionary step in the loss of gut protozoa in ancestral termitids [8]. We sequenced genomes and transcriptomes of 55 termite species and reconstructed phylogenetic trees from up to 4,065 orthologous genes of 68 species. We found strong support for a novel sister-group relationship between the bacterial comb-building Sphaerotermitinae and fungus comb-building Macrotermitinae. This key finding indicates that comb building is a derived trait within Termitidae and that the creation of a comb-like "external rumen" involving bacteria or fungi may not have driven the loss of protozoa from ancestral termitids, as previously hypothesized. Instead, associations with gut prokaryotic symbionts, combined with dietary shifts from wood to other plant-based substrates, may have played a more important role in this symbiotic transition. Our phylogenetic tree provides a platform for future studies of comparative termite evolution and the evolution of symbiosis in this taxon.